Strategi Adaptasi Nelayan Terhadap Perubahan Ekologis - Helmi, Alfian; Satria, Arif (UI Scholars Hub, 2012)
There is ambiguity on conducting sustainable development in coastal area. In fact, there are still virgin coastal areas, while some coastal areas have been exploited intensively across their carrying capacities. Beside environmental conservation efforts, some adaptation strategies for the fishermen to free the changes coastal areas are needed. The result of case study in Panjang Island, South Kalimantan shows that ecological changes were caused by land degradation of mangrove’s areas. The development of mangrove’s areas are the coal ports and shrimp ponds have changed their function as natural resource, especially as natural resource of community’s livelihood. Pulau Panjang is only approximately 5 Ha, but there are at least 7 coal ports arround its coastal area. Consequently, the fishermen have lost their fish stock and their livelihood. In response to the ecological changes, adaptation may play important role. The community should be able to respond the direct and indirect effects of the changes. In deed, the fishermen in Panjang Island have their own adaptation strategies that devide into economic strategy, political strategy and social strategy. The fishermen try to colaborate their sources of income, take the benefit of social connection and exploitate their other natural resource.